A new species of Ochna (Ochnaceae) from the Barberton Mountains of Mpumalanga, South Africa - Shah, Toral; Burrows, John; Darbyshire, Iain (Phytotaxa, 2018)
Ochna barbertonensis is described as a new species from the Barberton Mountains in Mpumalanga, South Africa. The new species is characterised by its suffrutescent habit, elongate-deltoid stipules sometimes with broadened base, mucronate leaf tip and high anther to filament ratio, where the anthers are ca. two times longer than the filaments. It is placed within sect. Ochna due to its poricidal anthers and subglobose drupes, attached at the base. It is most likely to be confused with the superficially similar suffrutescent species Ochna confusa, but that species has longitudinal anther dehiscence and anthers shorter than the filaments. The new species occurs within well protected nature reserves, but is only known from five collections with an Extent of Occurrence (EOO) of 34 km2, making it a ‘Rare’ species under the Red List of South African Plants. A species description, illustration and distribution map are provided.